"I felt that I deserved it" – experiences and implications of disability hate crime. Issue 2 (4th April 2016) - Richardson, Lisa; Beadle-Brown, Julie; Bradshaw, Jill; Guest, Colin; Malovic, Aida; Himmerich, Julian
Abstract : Purpose: – The purpose of this paper is to summarise key findings and recommendations from the "Living in Fear" research project focusing on the experiences of people with learning disabilities and autism related to disability hate crime and the experience of the police in dealing with such incidents. Design/methodology/approach: – Methods included: first, a postal survey with 255 people with learning disabilities or autism (or their carers for people with more severe disabilities), of whom 24 also took part in semi-structured interviews; and second, an electronic survey of the knowledge and experience of 459 police officers or support staff. Findings: – Just under half of participants had experienced some form of victimisation. The Police reported problems with the definition of disability hate crime and challenges to responding effectively. Social implications: – A case study from the research highlights some of the key findings and is linked to implications for people with learning disabilities and autism, carers, police and other agencies. Originality/value: – Previous research has highlighted that victimisation is an issue for this group of people, but has never explored the prevalence and nature of such experiences in a representative sample. Neither has previous research brought together the perspectives of so many different agencies to offer recommendations that go across many sectors. The paper will be of interest to people with disabilities and their carers, professionals in health, social care and the Criminal Justice system.